AKIBAT HUKUM PERCERAIAN TERHADAP PEMBAGIAN HARTA BERSAMA BERDASARKAN KOMPILASI HUKUM ISLAM DI (KELURAHAN TANAH TINGGI, KECAMATAN TAPUNG HILIR, KABUPATEN KAMPAR ) - Frizka Lystari Limbong; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Man is a creation of God who has various needs in his life and every manwould want fulfillment of his needs properly to be able to live as a perfect human,both individually and as part of the community. Marriage is a necessity of life forall humanity, from ancient times until now. Because marriage is an actual issue totalk about within and outside the legal arena. From marriage there will be a legalrelationship between husband and wife and then with the birth of children,resulting in a legal relationship between parents and their children. Frommarriage they have property, and there will be a legal relationship between themwith the property.In the division of joint property as a result of divorce the Compilation ofIslamic Law also explains in Article 97 KHI which says that the widow ordivorced divorce each shall be entitled to equal to the common property as longas no other specified in the marriage agreement. Unlike the case in the communityprecisely in Kelurahan Tanah Tinggi, Tapung Hilir District, Kampar Districtwhich is the author's research area, where the author finds the problem, wherethe problem is different from the provisions that should apply. In this case foundthe case that a widow does not get her right in terms of sharing of joint propertyafter divorce with her husband.Budi's son got part of Palm Oil Plantation, and his daughter love to getpart 1 Unit Rumah .. While the wife did not get part of the marriage property.Seeing the above reality, the writer considers it is a problem that needs to bestudied and got a legal solution. Therefore, the authors are interested to conductresearch titled Due to Divorce Law on the Division of Joint Treasure Based onthe Compilation of Islamic Law.Keywords : Divorce-Division of Joint Treasure-Compilation of Islamic Law